Developments in information security and cybernetic wars - Sarfraz, Muhammad (IGI Global, 2019)
"This book focuses on cyber warfare and terrorism using examples from around the world. It covers technical aspects, management issues, social issues, and government issues that relate to cyber warfare and terrorism"--